The relationship between body temperature, heart rate, breathing rate, and rate of oxygen consumption, in the tegu lizard (Tupinambis merianae) at various levels of activity - Piercy, Joanna (2015)
The present study determined whether EEG and/or EMG recordings could be used to reliably define activity states in the Brazilian black and white tegu lizard (Tupinambis merianae) and then examined the interactive effects of temperature and activity states on strategies for matching O-2 supply and demand. In a first series of experiments, the rate of oxygen consumption (), breathing frequency (f (R)), heart rate (f (H)), and EEG and EMG (neck muscle) activity were measured in different sleep/wake states (sleeping, awake but quiet, alert, or moving). In general, metabolic and cardio-respiratory changes were better indictors of the transition from sleep to wake than were changes in the EEG and EMG. In a second series of experiments, the interactive effects of temperature (17, 27 and 37 A degrees C) and activity states on f (R), tidal volume (V (T)), the fraction of oxygen extracted from the lung per breath (FIO2-FEO2), f (H), and the cardiac O-2 pulse were quantified to determine the relative roles of each of these variables in accommodating changes in . The increases in oxygen supply to meet temperature- and activity-induced increases in oxygen demand were produced almost exclusively by increases in f (H) and f (R). Regression analysis showed that the effects of temperature and activity state on the relationships between f (H), f (R) and was to extend a common relationship along a single curve, rather than separate relationships for each metabolic state. For these lizards, the predictive powers of f (R) and f (H) were maximized when the effects of changes in temperature, digestive state and activity were pooled. However, the best r (2) values obtained were 0.63 and 0.74 using f (R) and f (H) as predictors of met abolic rate, respectively.